Perfil epidemiológico da mortalidade na área vermelha em um hospital de urgência do Estado de Sergipe - Santos, Vinicius Rafael Souza (2015)
Objectives: to trace the epidemiologic, sociodemographic and clinical profile of mortality in the HUSE’s Red Area utilizing the OPO’s data as a source and to analyze the relationship between one and four Causes of death. Methods: Cross-sectional descriptive study of all deaths in the HUSE’s Red Area in the years 2013 and 2014. Main results: In this study were analyzed 2451 deaths, 58% (n = 1421) were for men and 42,0% (n = 1030) women. The average age was 59,9 anos (DP ± 20,4). It was found greater lost data in five Cause (90,4%) and lowest in one Cause (12,8%). Infectious diseases and ill- defined causes represented 47,7% (n = 1021) of deaths in one Cause. When performing association analysis it was found that the Infectious Diseases are the first or second largest Cause of death in 10 of 11 four Cause. Conclusion: Infectious Diseases have great impact on mortality in the Area. Moreover, OPO’s data may serve as an alternative source for the study of Hospital Mortality.